Children's social network size is related to their perspective-taking skills - Burke, Nicole; Brezack, Natalie; Meyer, Marlene; Woodward, Amanda (Frontiers in Developmental Psychology, 2023)
Perspective-taking (PT) is an important skill children develop within the first few years of life; however, little is known about how children's social environments relate to PT development. During early childhood, children's social networks undergo dramatic growth (Burke et al., 2022). Prior work with adults has shown that network size is related to PT skill, which raises the question of whether and how children's social networks may relate to their emerging PT skills. This question is particularly interesting given that children's social worlds undergo dramatic growth and changes, which is a sharp contrast from adults that have stable social network sizes. The present study measured the social networks of 3-year-old children (n = 36; 15 female; 68% White) and found that children in larger social networks demonstrated stronger PT skills, particularly on the more difficult trials on the task. These results indicate the size of children's social networks relates to their PT ability.